Earth (the book) : a visitor's guide to the human race - Stewart, Jon, 1962- (New York : Grand Central Pub., 2010)
Presents a humorous summation of the history of humanity and our achievements in society, government, religion, science, and culture.
At head of title: The Daily show with Jon Stewart presents.
Keywords: Civilization -- Humor; Human beings -- History -- Humor; Civilization -- Humor; Human beings -- History -- Humor